Purchases and Wellbeing of Older and Younger Adults in Tomsk; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 7 : Lifelong Wellbeing in the World (WELLSO 2015) - Kashapova E. R. Elmira Ramisovna; Ryzhkova M. V. Marina Vyacheslavovna; Gustap N. Nalatia; Nikitina S. S. Svetlana Sergeevna (2016, 2016)
Title screen